Does Tobacco Use Attenuate Benefits of Early Decompression in Patients With Cervical Myelopathy?. Issue 20 (15th October 2016) - Kusin, David J.; Li, Samuel Q.; Ahn, Uri M.; Ahn, Nicholas U.
Abstract : Study Design: A retrospective cohort. Objective: This study investigates the interplay between duration of preoperative symptoms and smoking status with respect to postoperative outcomes in patients with cervical spondylotic myelopathy (CSM). Summary of Background Data: Many studies have established the harms of smoking and several have identified the benefits of early decompression in patients with cervical myelopathy, but to our knowledge, none have assessed the relationship between these two variables. Methods: The medical records of all 212 patients operated on by the senior author between March 2005 and July 2012 were reviewed. Inclusion criteria were the diagnosis of CSM with a Nurick score, surgical intervention, and at least 2 years of follow-up. Patients were categorized according to smoking status and quantification of tobacco use by packs per day and pack-years, and duration of symptoms according to thresholds of 6, 12, or 24 months. Age, sex, preoperative Nurick score, duration of preoperative symptoms, duration of follow-up, procedure performed, prior surgery, number of levels operated on, diabetes status, ethanol use, and signal change on preoperative magnetic resonance imaging were also recorded for ordered logistical regression analysis. Results: One hundred twenty-five patients met all criteria. Eighty patients were smokers and 45 were nonsmokers. The median change in Nurick score for nonsmokers was 2 compared with 1 in smokers. Nonsmokers had a statistically significant likelihood of decreased change in Nurick score for symptom duration of greater than 24 months (odds ratio = 0.06, P = 0.0025). Smokers did not show a significant difference in the change in Nurick score for any threshold of symptom duration. Conclusion: Increased duration of symptoms significantly affects outcomes in surgical decompression of CSM. A history of cigarette use may attenuate the benefit of early decompression and results in lower improvement in Nurick score regardless of symptom duration. Level of Evidence: 3